The prevalence and impact of debilitative psychological and behavioral responses to long-term injury in athletes - Gervis, M.; Pickford, H.; Nygârd, H.; Goldman, A. (Journal of Clinical Sport Psychology, 2023)
Injuries, and their psychological and maladaptive behavioral consequences, are an inevitable by-product of sport participation. This study sought to investigate the prevalence of maladaptive behaviors and psychological corollaries of long-term injury in order to understand if these are universal experiences of long-term injured athletes. Competitive athletes (n = 187; average time spent injured =43 weeks), across a range of sports completed an online questionnaire developed to investigate the psychological and behavioral consequences of long-term injury. Results indicated that negative symptoms after injury were a universal experience and are the "normal" response to injury, not the "exception." The most prevalent psychological consequences were rumination (97.9%), boredom (94.7%), and fear of reinjury (93.6%). Furthermore, indicators of suicidal ideation were reported by more than 50% of participants. Factor analysis revealed a six-factor model: (a) self-sabotaging behavior, (b) daily functioning, (c) addictive behavior, (d) clinical issues, (e) fixation on injury, and (f) compromised athletic identity. All factors significantly correlated with debilitating impact. Thus, this study calls for a change to the support of long-term injured athletes to include routine psychological care.